Associations between daily cooking duration and the prevalence of diabetes and prediabetes in a middle‐aged and elderly Chinese population: A cross‐sectional study. (27th November 2017) - Wang, F.; Wang, J.; Li, Y.; Han, X.; Hu, H.; Yu, C.; Yuan, J.; Yao, P.; Miao, X.; Wei, S.; Wang, Y.; Chen, W.; et al.
Abstract: Experimental and epidemiological studies indicated that ambient air pollution was positively associated with diabetes. Few studies investigated the associations between household air pollution, for example, daily cooking duration and diabetes or prediabetes. We conducted a cross‐sectional study to investigate the associations of daily cooking duration with the prevalence of diabetes and prediabetes among a middle‐aged and elderly population. A total of 26 089 individuals (11 250 males and 14 839 females) derived from the Dongfeng‐Tongji cohort study were included. Daily cooking duration was assessed by questionnaire. Diabetes and prediabetes were identified according to the criterion of American Diabetes Association. No significant association was observed between daily cooking duration and the prevalence risk of diabetes (odds ratio[OR] = 0.97, 95% confidence interval[CI]: [0.81‐1.16], P for trend = .74); however, longer daily cooking duration was associated with higher prevalence risk of prediabetes (OR = 1.26, 95% CI: 1.07‐1.47; P for trend = .003) and hyperglycemia (OR = 1.21, 95% CI: 1.05‐1.41; P for trend = .005). Our study suggested that daily cooking duration was not associated with diabetes but with higher prevalence risk of prediabetes/hyperglycemia in a middle‐aged and elderly Chinese population.